The keystone of Alzheimer pathogenesis might be sought in Aβ physiology. (29th October 2015) - Puzzo, D.; Gulisano, W.; Arancio, O.; Palmeri, A.
Highlights: Physiological concentrations of Aβ are needed for synaptic function. Alzheimer's disease might be due to a dysregulation of Aβ physiological homeostasis. The increase of Aβ might be due to an alteration of the feedback loop between Aβ and α7-nAchRs. Amyloid Cascade Hypothesis should be revisited. Abstract: For several years Amyloid-beta peptide (Aβ) has been considered the main pathogenetic factor of Alzheimer's disease (AD). According to the so called Amyloid Cascade Hypothesis the increase of Aβ triggers a series of events leading to synaptic dysfunction and memory loss as well as to the structural brain damage in the later stage of the disease. However, several evidences suggest that this hypothesis is not sufficient to explain AD pathogenesis, especially considering that most of the clinical trials aimed to decrease Aβ levels have been unsuccessful. Moreover, Aβ is physiologically produced in the healthy brain during neuronal activity and it is needed for synaptic plasticity and memory. Here we propose a model interpreting AD pathogenesis as an alteration of the negative feedback loop between Aβ and its physiological receptors, focusing on alpha7 nicotinic acetylcholine receptors (α7-nAchRs). According to this vision, when Aβ cannot exert its physiological function a negative feedback mechanism would induce a compensatory increase of its production leading to an abnormal accumulation that reduces α7-nAchR function, leading to synaptic dysfunction and memory loss. In this perspective, the indiscriminate Aβ removal might worsen neuronal homeostasis, causing a further impoverishment of learning and memory. Even if further studies are needed to better understand and validate these mechanisms, we believe that to deepen the role of Aβ in physiological conditions might represent the keystone to elucidate important aspects of AD pathogenesis.